SYNTHESIS AND SPECTROSCOPIC CHARACTERIZATION OF SOME NEW HYDROGENOXALATO ORGANOTIN (IV) COMPLEXES - MOUHAMADOU SEMBENE BOYE; AMINATA DIASSE-SARR; LIBASSE DIOP (Journal of Engineering Studies and Research)
The synthesis and spectroscopic studies (infrared and Mössbauer) of new hydrogenoxalato derivatives and adducts containing SnRn (R=Me, Ph; n=2, 3) residues are reported. Based on their spectroscopic data dimeric and polymeric structures containing hexacoordinated or pentacoordinated Sn are suggested, the hydrogenoxolate anion behaving as a monocoordinating or a monochelating ligand. In two studied adducts, supramolecular architectures may be obtained when extra hydrogen bonds involving the free NH groups are considered.